Distinct T helper cell-mediated antitumor immunity: T helper 2 cells in focus - Rafael Cardoso Maciel Costa Silva; Marcela Freitas Lopes; Leonardo Holanda Travassos (Cancer Pathogenesis and Therapy, 2023)
The adaptive arm of the immune system is crucial for appropriate antitumor immune responses. It is generally accepted that clusters of differentiation 4+ (CD4+) T cells, which mediate T helper (Th) 1 immunity (type 1 immunity), are the primary Th cell subtype associated with tumor elimination. In this review, we discuss evidence showing that antitumor immunity and better prognosis can be associated with distinct Th cell subtypes in experimental mouse models and humans, with a focus on Th2 cells. The aim of this review is to provide an overview and understanding of the mechanisms associated with different tumor outcomes in the face of immune responses by focusing on the (1) site of tumor development, (2) tumor properties (i. e., tumor metabolism and cytokine receptor expression), and (3) type of immune response that the tumor initially escaped. Therefore, we discuss how low-tolerance organs, such as lungs and brains, might benefit from a less tissue-destructive immune response mediated by Th2 cells. In addition, Th2 cells antitumor effects can be independent of CD8+ T cells, which would circumvent some of the immune escape mechanisms that tumor cells possess, like low expression of major histocompatibility-I (MHC-I). Finally, this review aims to stimulate further studies on the role of Th2 cells in antitumor immunity and briefly discusses emerging treatment options.